DIATESIS (TAI) DALAM BAHASA JEPANG (TINJAUAN DALAM BUKU MINNA NO NIHONGO) - Parwati Hadi Noorsanti (Universitas Negeri Surabaya, 2017)
Diathesis is a grammatical category that shows the relationship between the participant or the subject with the action expressed by the verb in the clause. In the book Minna no Nihongo I and II there are several types of sentences containing diathesis. This type of diathesis is often quite difficult for a Japanese learner. In this theoretical study paper the author describes the meaning of diathesis sentences contained in Minna no Nihongo I and Minna no NihongoII books used in basic and intermediate Japanese language learning. With this paper is expected to increase the understanding of learners of Japanese diathesis sentences. The types of diathesis sentences analyzed are judoutai (passive diathesis), Shieki (causative), kanoutai (potential form) and jujuhyougen (giving and receiving phrases). In addition to understanding the structure of diathesis, some things that the learner needs to understand, among others, in the passive diagrams sentence (vocabulary) verbs or actions centered on objects not actors, in causative sentences (Shieki), verbs that can be used as a causative form are verbs States the type of meaning of action or change (active verb), in understanding the form of sentence jujuhyougen, the learner must understand that in the sentence using jujuhyougen expression contained the meaning of gratitude or gratitude because the offender or subject sentence gets the good of others.